Kewajiban Perusahaan Pertambangan Dalam Reklamasi Lahan Tambang Menurut Undang-Undang Nomor 3 Tahun 2020 Tentang Pertambangan Mineral Dan Batubara - Diaz Rahadiyan Rizkirobbi; Nurul Listiyani; Iwan Riswandie (Scholar Center, 2022)
Aside from the rise of environmental issues regarding mining activities, especially in the context of reclamation and post-mining activities, there have been changes in the regulations governing them. The reclamation program for ex-mining land is a mandatory program that must be carried out by every company, both private and non-private. Reclamation is an activity carried out throughout the mining business stages to organize, restore, and improve the quality of the environment and the ecosystem so that they function again according to their designation. The placement of post-mining guarantees by companies should not eliminate the company's obligation to carry out post-mining activities. If the company has a shortage of reclamation planning costs, placement of reclamation guarantees, implementation of reclamation, or release or disbursement of reclamation guarantees to complete post-mining activities under the stipulated guarantee, it remains the company's responsibility.